A 3D Fluid Dynamic Rendering For Real-Time Surgical Cutting Simulation - Sugeng Rianto (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2008)
In this paper, we introduce a 3D fluid dynamics solver for real-time rendering in virtual environment.We approach the solution of differential equations based on the constrained interpolation propagation(CIP) technique on a GPU. Since the CIP combine the solution for fluid equations and their interactions withthe environment together, the Navier-Stokes equation can be solved efficiently. Furthermore, to achieve highperformance results for real time rendering without involving a supercomputer, we take advantages of theparallelism and programmability on the GPU. The rendering is performed on pixels that can be considered tobe a grid of cells; thus, processing on multiple vertices and pixels can be done simultaneously in parallel. Thisstrategy is effective enough to render fluid dynamic model for real-time virtual cutting in 3D computer generatedobject. Experimental results demonstrate that the rendering of skin cutting followed by blood flowing over theanatomical surface run smoothly in a real-time for virtual reality interaction.Keywords: Cutting simulation, fluid dynamic, real time rendering, virtual surgery.